Effects of land abandonment on plant litter decomposition in a Montado system: relation to litter chemistry and community functional parameters - Castro, Helena; Fortunel, Claire; Freitas, Helena (Plant and Soil, 2010)
Changes in land use and subsequent shifts in vegetation can influence decomposition through changes in litter quality (chemistry and structure) and alterations of soil temperature and moisture. Our aim was to study the effects of land abandonment on litter decomposition in a Mediterranean area of Montado, South Portugal. We tested the hypothesis that decomposition tends to slow down with abandonment, as woody species, richer in lignified structures, replace herbaceous species. We assessed the decomposition of community litter in situ using litterbag technique. To test the influence of local conditions, we simultaneously incubated a standard litter in situ. Our results showed that the shift from herbaceous to shrubdominated communities lead to decreased decomposition rates. Changes in litter decomposition were primarily driven by changes in litter quality, even though the uneven pattern of litter mass loss over the experiment might reveal an effect from possible differences in microclimate. Shrub litter had higher nutrient content than herbaceous litter, which seemed to favour higher initial decomposition rates, but lower decomposition rate in the longer term. Shrubs also contribute to woody litter, richer in lignin, and secondary compounds that retard decomposition, and may play a role in increasing pools of slowly decomposing organic matter.
Keywords: ecosystem processes; Land use change; leaf dry matter content; Life form; litter quality; Mediterranean